The level of cultural intelligence among faculty members in Jordanian private universities from the students’ point of view - Al-Baher, Ibrahim Ali; Al-Maaitah, Eman sager; Mohammad, Israa Abdallah; Obeidat, Nebal Abdel Razzaq; Fraihat, Nesreen Bassam (Technium Social Sciences Journal, 2022)
The study aimed to know the level of cultural intelligence among faculty members in Jordanian private universities from the students’ point of view, the study used the descriptive survey method, The study sample consisted of (200) male and female students who were selected in a stratified random manner , The study tool was represented by a questionnaire that consisted of (40) items distributed on (3) areas: Behavioral cultural intelligence, motivational cultural intelligence, and cognitive cultural intelligence. The results of the study showed that the level of cultural intelligence among faculty members in Jordanian private universities from the students’ point of view was average, with an arithmetic mean of (3.35). The results of the study showed that there were no statistically significant differences in the scale of the level of cultural intelligence among faculty members according to the variable of gender and college, The results of the study also indicated that there were no statistically significant differences according to the educational qualification variable in the areas of behavioral, motivational and cognitive cultural intelligence. And to the existence of statistically significant differences in the field of cultural-behavioral intelligence and in favor of the postgraduate qualification holders.